School climate and peer victimization: perceptions of students with intellectual disability - Hellen Tsuruda Amaral; Josafá Moreira da Cunha; Iasmin Zanchi Boueri; Jonathan Bruce Santo (Universidade Federal de Santa Maria (UFSM), 2021)
Considering the experiences of students with intellectual disabilities (ID) in educational environments, peer victimization stands out for potential losses to development. This is a relationship problem, which requires an understanding of contextual factors. In the approach of the authoritative school climate, the perception of support and disciplinary structure act as possible attenuators of peer victimization. However, the association between school climate and victimization is rarely examined in samples with people with ID. Thus, the study aimed to examine the associations between authoritative school climate and peer victimization through a procedure accessible to the self-report of people with ID. It was hypothesized that the disciplinary structure and support would be negatively associated with victimization. The study included 117 students with ID, aged between 12 and 63 years (mean=25.31; sd =12.25); 62.4% of male participants; 56.9% white and 54.1% diagnosed with moderate DI. The measures and procedures went through a cognitive accessibility process to enable the participation of students with ID through self-report, the data were analyzed using structural equation modeling. The adaptation was partially successful. In the final model, the disciplinary structure was positively correlated to support, which was a negative predictor for victimization. The results highlight how school environments with a supportive school climate can be a protective factor in relation to the victimization of people with ID, and that more inclusive practices in scientific research are possible.